2022
DOI: 10.1213/ane.0000000000005980
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia Associated With Decreased Inpatient and Outpatient Opioid Demand in Tibial Plateau Fracture Surgery

Abstract: BACKGROUND: Regional anesthesia (RA) has been used to reduce pain and opioid usage in elective orthopedic surgery. The hypothesis of this study was that RA would be associated with decreased opioid demand in tibial plateau fracture surgery. METHODS: Inpatient opioid consumption and 90-day outpatient opioid prescribing in all patients ≥18 years of age undergoing tibial plateau fracture surgery from July 2013 to July 2018 (n = 264) at a single, level I trauma center were recorded. The presence or absence of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…If the patient has the symptoms of joint swelling and limitation of movement, the joint, joint space, and meniscus feel tenderness during physical examination, MRI examination shows meniscus grade III signal changes; combined with arthroscopy, the existence of meniscus injury can be comprehensively determined. (2) Determination of ligament injury [ 12 ]: ligament injury can be divided into two types: collateral ligament injury and cruciate ligament injury. (3) Determination of osteoporosis [ 13 ]: the existence of osteoporosis was determined by whole body bone mineral density (BMD).…”
Section: Methodsmentioning
confidence: 99%
“…If the patient has the symptoms of joint swelling and limitation of movement, the joint, joint space, and meniscus feel tenderness during physical examination, MRI examination shows meniscus grade III signal changes; combined with arthroscopy, the existence of meniscus injury can be comprehensively determined. (2) Determination of ligament injury [ 12 ]: ligament injury can be divided into two types: collateral ligament injury and cruciate ligament injury. (3) Determination of osteoporosis [ 13 ]: the existence of osteoporosis was determined by whole body bone mineral density (BMD).…”
Section: Methodsmentioning
confidence: 99%
“…The targeted pain relief improves pain scores while decreasing opioid use, side effects from systemic medications, lengths of stay, and health care costs. 14 Many enhanced recovery after surgery (ERAS) and injury protocols include regional anesthetics in multimodal care. 25 In patients at risk for ACS, PNB may provide added benefits by limiting catecholamine release and enhancing blood flow through the extremity via sympathetic blockade.…”
Section: Pro: Modified Pnb Should Be Used Routinely In Extremity Trau...mentioning
confidence: 99%
“…13 Traditionally, systemic opioid analgesia has been used for severe trauma-related pain despite numerous side effects and the risk of creating opioid dependence when pain is uncontrolled. 14 Alternative analgesic modalities have been introduced with PNB providing superior analgesia and improved range of motion tolerance with minimal to no side effects. 1 High-energy injuries, fractures (particularly tibial plateau, tibial shaft, and radial fractures), or vascular trauma also predispose the patient to a greater likelihood of developing ACS.…”
Section: Introductionmentioning
confidence: 99%
“…When determining how to manage acute orthopedic trauma pain, one must tailor it to the type of injury and intervention as it has been shown that fracture location, tissue involvement, and operative fixation have significant effects on pain intensity [32]. Elective orthopedic surgeries utilizing RA have reduced opioid consumption and postoperative pain; however, traumatic fractures are commonly associated with bone and soft tissue trauma which may be associated with increased inflammation and pain patterns [ ].…”
Section: Orthopedic Traumamentioning
confidence: 99%